Psychological effects of COVID-19 phobia on industrial consumers: a case study in Turkey - Degirmenci, Bekir; Durmaz, Yakup; Fidanoglu, Ahmet; Degirmenci, Sibel (EMERALD GROUP PUBLISHING LTD)
Purpose This study aims to discover whether COVID-19 phobia has a positive and significant effect on the stress, depression and anxiety levels of industrial consumers in addition to reveal whether environmental awareness plays a mediating role between COVID-19 phobia and stress, depression and anxiety. Design/methodology/approach In this study, a quantitative method was used to reveal the role of anxiety, depression and stress (psychological effects) and environmental awareness caused by covid-19 phobia on industrial consumers. The universe of the study is small and medium-sized enterprises operating in the province of Sanliurfa, which is located in the southeast region of Turkey and the second largest city in the region, and are industrial customers. Questionnaire method was used in the study. In addition, data were collected from 406 people who agreed to participate in the study. In the study, in which intermediary and regulatory analyzes were made, the process macro program was used. Findings The results show that there is a medium relationship between COVID-19 phobia and environmental awareness; and COVID-19 phobia and stress, depression and anxiety. No relationship was found between environmental awareness and stress, depression and anxiety. COVID-19 phobia was found to have a positive and significant effect on environmental awareness and stress, depression and anxiety, while environmental awareness was found to have no effect on stress, depression and anxiety. Finally, environmental awareness was found to play a mediating role between COVID-19 phobia and stress, depression and anxiety. Research limitations/implications In this study, four hypotheses were developed. Of these hypotheses, three are for the simple effect and one for the mediation effect. Out of four hypotheses, three were supported. The most important inference obtained from the study was finding the mediation effect of environmental awareness between COVID-19 phobia and anxiety, depression and stress. Originality/value To the best of the authors' knowledge, no studies in the literature were made on the relationship among COVID-19 phobia, environmental awareness, stress, depression and anxiety. This study also examines the mediating effect of environmental awareness in the relationship between COVID-19 phobia and stress, depression and anxiety. The fact that the study is on the negative effects of the pandemic on one of the most affected occupational group also increases its original value.
Keywords: Industrial customer; Environmental awareness; Stress; Depression; Anxiety; COVID-19 phobia